Does Religious Learning Affect Saving Intention in Islamic banks? An Empirical Evidence from High School Alumni in Jakarta - Mohamad Soleh Nurzaman; Toyyib Hidayah (Talaa : Journal of Islamic Finance, 2024)
Indonesia is one of the countries with the largest Muslim population in the world, but the number of Islamic bank customers is still small compared to conventional banks. Although there have been many studies that have tried to identify factors that influence intention in saving in Islamic banks, none have discussed the role of religious learning in high schools. Therefore, this study aims to determine whether there is an effect of compulsory Islamic religious learning for 3 years at the high school level on saving intention in Islamic banks. This study uses a quantitative method by taking a sample of 125 alumni of State High Schools in Jakarta who graduated in 2020-2023, which were then analyzed using the Partial Least Square Structural Equation Model (PLS-SEM). Based on the Theory of Reasoned Action (TRA) used, the results of this study indicate that Islamic religious learning provided during school has a significant effect on saving intention in Islamic banks. Meanwhile, the variables of religiosity, attitude, and subjective norms also have an effect, with a higher significance value, on interest in saving in Islamic banks.